SOLVING LARGE SCALE TRANSPORTATION PROBLEM IN FERTILIZER DISTRIBUTION TO MINIMIZE TRANSPORTATION COST - Angga Akbar Fanani; Arif Rahman; Astuteryanti Tri Lustyana; Sri Widiyawati (Journal of Engineering and Management in Industrial System, 2022)
Indonesia is agricultural country which have high degree of dependency to the fertilizer availability, it is because fertilizer has important role for the land fertility. Fertilizer is needed by the farmers all the time, from the initial period of planting the crop to the harvest period. This condition requires the fertilizer industry to be able to deliver fertilizer exactly when fertilizer is needed. The complexity of the transportation problem is indicated by the number of nodes in the model that represent both source and destination. In the distribution of fertilizer, the number of sources is relatively small, but the number of destinations is very large, where the number reaches 50 destination points. In solving large scale transportation complex problems, modeling techniques using Linier Programming are needed. Fertilizer demands are fulfilled from 42 buffer warehouses, and the optimal allocation for petrochemical distribution is supplied by 47 production partners. Based on the results of the calculation process using linier programming, the optimal distribution cost is 939,854,960.00 rupiahs. Meanwhile, the initial cost of distribution is IDR 1,032,267,660.00. There was a decrease of 92,412,700.00 rupiahs or about 9%. Optimization of the distribution process is also marked by the decrease in the number of production partners needed to meet the needs of 42 buffer warehouses. In the initial distribution, 56 production partners sent their products, after the calculation process only 47 production partners were needed.